If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+4)=(x+4)2
We move all terms to the left:
2(x+4)-((x+4)2)=0
We multiply parentheses
2x-((x+4)2)+8=0
We calculate terms in parentheses: -((x+4)2), so:We get rid of parentheses
(x+4)2
We multiply parentheses
2x+8
Back to the equation:
-(2x+8)
2x-2x-8+8=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 10h/20=0.5 | | 2,5/1,24=x/6,2 | | 25x+29=-3 | | 4x-30=x*6 | | 4m-3=13(m-4) | | 18x-3=5x+8 | | 6.6x-60=20+6x | | a2=836 | | B+8+2b+7+b+b=6b+3 | | b2=128 | | 2+3m-9=-7 | | 1.4+x÷6=2.4 | | 3a-4+7a+10=126 | | 180=3y | | 7p-2p=3p+20 | | 21/(m+7)+14=2m | | z/4+5=-7 | | 10p-1=2p+19+3p | | (6p+5)=(5+6p) | | 8x2+6x+1=0 | | 3(z−18)=6 | | 63,000=x10 | | 63,000=x104 | | 9k-10=5k+10 | | 9k-10=5k=10 | | 3x+5=2*3 | | -2(x-3)=3(1+2x) | | x+6=9+3x | | 7x=70−3x | | 4*x+4=20 | | 4^4-5x^2+7=0 | | 6=1x/5 |